Platform for spectrally resolved x-ray scattering from imploding capsules at the National Ignition Facility. (May 2016) - Kraus, D; Döppner, T; Kritcher, A L; Yi, A; Boehm, K; Bachmann, B; Divol, L; Fletcher, L B; Glenzer, S H; Landen, O L; Masters, N; Saunders, A M; et al.
Abstract: We present a new experimental platform to perform spectrally resolved x-ray scattering measurements of ionization, density and temperature in imploding CH or beryllium capsules at the National Ignition Facility. Scattered x-rays at 9 keV from a zinc He-alpha plasma source at a scattering angle of 120 degrees are highly sensitive to K-shell ionization, while at the same time constraining density and temperature. This platform will allow for x-ray scattering studies of dense plasmas with free electron densities up to 10 25 cm -3 giving the possibility to investigate effects of pressure ionization and Pauli blocking on the ablator ionization state right before or shortly after stagnation of the implosion.